ANALYSING THE EFFECT OF FOULING ON A CROSS FLOW MICRO HEAT EXCHANGER - Bayo-Philip P; Layiwola, O. A (International Journal of Innovations in Engineering Research and Technology, 2022)
Heat exchangers as a heat transfer device have gained wide applications across different levels of domestic and industrial set-ups. The fouling formation in heat transfer equipment is the complex process, which is determined by the physical properties of the heat carrier, material of the unit and hydraulic characteristics of the flow. The mathematical model based on the asymptotic behaviour of water fouling is examined. The objective of this project is to study the effect of fouling on a cross flow heat exchanger. A theoretical approach showing the effect of fouling has been developed. This approach is based on the basic fouling deposition. The outer and inner rate of fouling relationship was shown. The rate of fouling was kept constant at 0.0007 to 0.00009 and its result is shown. As it can be observed the heat transfer coefficient has affected the heat exchanger adversely. The developed model can be used as a very useful tool in the design and operation of the heat transfer equipment by controlling the parameters affecting fouling processes. The heat transfer coefficient of the inlet diameter is calculated as 4.99*10^5 WM2/K and the outlet diameter heat transfer is 1.76 WM2/K. The fouling formation in heat transfer equipment is the complex process and this process determines the heat transfer coefficient and the mass flow rate of the shell and tube.